Covid-19 Effect to A Conventional and IBS Construction Project at Kuala Lumpur, Malaysia - AINUAL AZHAR, MOHAMAD HAFIZ SYAMIL; Hasmori, Mohd Fikri (Recent Trends in Civil Engineering and Built Environment, 2022)
The Covid-19 epidemic caused widespread worldwide disruption. Forcing lockdowns in several countries, including Malaysia, in an effort to stop the virus from spreading. As an initiative, the Malaysian government come out with Movement Control Order (MCO) as one of the lockdown choices, started on March 18, 2020. As a result, the MCO had a massive impact on the Malaysian industrial sector, including the construction industry. This study aims to investigate the effect Covid-19 to a conventional and industrialized building system (IBS) construction project. Besides that, the scope of this study conducted based in Kuala Lumpur, Malaysia.  The data collected were analyzed by Statistical Package Social Science (SPSS) and Average Index Analysis. Frequency analysis was used to identify the effect of the Covid-19 pandemic in the construction industry. The questionnaires were distributed after conducted the expert review and pilot study. The statistical significance index method was used to measure the awareness of the Covid-19 prevention measure at the construction site. The study found most respondents acknowledge Covid-19 and the spreading among people, acknowledge workers about Standard Operation Procedure (SOP) during MCO at the construction site, and also employer provides sanitation station before entering the construction site. In addition, this study also found the conventional project method was the most affected due Covid-19 outbreak than the IBS project method. The findings help employer, site safety officer to realize the sequences of the sudden epidemic and prepare for the worst-case scenario during the planning stage of the construction projects